Metabolic disorders in patients with chronic thromboembolic pulmonary hypertension - Sergey Yu. Yarovoy; Nikolay M. Danilov; Galina V. Shchelkova; Ekaterina O. Dinevich; Anastasiya A. Mitrofanova; Irina E. Chazova (Терапевтический архив, 2024)
Aim. To analyze the relationship between metabolic disorders and obesity with hemodynamic parameters and the severity of the condition of patients with chronic thromboembolic pulmonary hypertension (CTEPH) based on the POLET register.